Some trouble with cows : making sense of social conflict - Roy, Beth (University of California Press, 1994)
Fascinating in its combination of personal stories and analytical insights, Some Trouble with Cows will help students of conflict understand how a seemingly irrational and archaic riot becomes a means for renegotiating the distribution of power and rights in a small community. Using first-person accounts of Hindus and Muslims in a remote Bangladeshi village, Beth Roy evocatively describes and analyzes a large-scale riot that profoundly altered life in the area in the 1950s. She provides a rare glimpse into the hearts and minds of the participants and their families, while touching on a range of.